Advanced cognitive networked radar surveillance - Jahangir, Mohammed; Baker, Chris J.; Antoniou, Michail; Griffin, Benjamin; Balleri, Alessio; Money, David; Harman, Stephen (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The concept of a traditional monostatic radar with co-located transmit and receive antennas naturally imposes performance limits that can adversely impact applications. Using a multiplicity of transmit and receive antennas and exploiting spatial diversity provides additional degrees of design freedom that can help overcome such limitations. Further, when coupled with cognitive signal processing, such advanced systems offer significant improvement in performance over their monostatic counterparts. This will also likely lead to new applications for radar sensing. In this paper we explore the fundamentals of multistatic network radar highlighting both potential and constraints whilst identifying future research needs and applications. Initial experimental results are presented for a 2-node networked staring radar.
Keywords: Networks; Multistatic; Distributed; Cognitive; Intelligent; Radar